1997
DOI: 10.1002/(sici)1099-1166(199712)12:12<1151::aid-gps700>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Screening for alcohol misuse in older people

Abstract: The results confirm previous UK studies which indicate that the CAGE and an abnormally high MCV are poor screening instruments for alcohol misuse in older patients and also indicate that the MAST-G is an insensitive screening instrument. A new two-step instrument with five questions in total was generated. This requires further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The ®gures, however, may still be an underestimate given that elderly substance misusers often go undetected during hospital admission (Luttrell et al, 1997). The indirect references to data published 25 years earlier illustrate the lack of recent work in this ®eld.…”
Section: Hospital Samplesmentioning
confidence: 98%
See 1 more Smart Citation
“…The ®gures, however, may still be an underestimate given that elderly substance misusers often go undetected during hospital admission (Luttrell et al, 1997). The indirect references to data published 25 years earlier illustrate the lack of recent work in this ®eld.…”
Section: Hospital Samplesmentioning
confidence: 98%
“…For example, it is conceivable that the eect of prohibition may have in¯uenced the drinking practices of the cohort of Americans now entering old age. Similarly, the way in which subjects answer screening questions may dier between North America and other countries, aecting the relative sensitivities of screening instruments (Luttrell et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The MAST-G is more widely used in the USA, but is not well validated, especially in European populations. There has only been one UK study (Luttrell et al, 1997), which showed sensitivity of only 50 per cent. One reason given for this is that the MAST-G is a screening tool developed among older adult populations in the USA may not translate well culturally in the UK population.…”
Section: Screening Toolsmentioning
confidence: 99%
“…Furthermore, most measures are designed for detection of alcohol abuse problems in the younger adult population. Additional measures designed specifically for older adults have been created (e.g., the UCLS; Luttrell et al, 1997) , but further validation is needed. The CAGE (Mayfield, 1974) , although not specifically designed for older adults, appears to be suitable for use in this population.…”
Section: Assessment Of Cognitive Functioningmentioning
confidence: 99%